Corticotropin-releasing hormone modulates NREM sleep consolidation through the thalamic reticular nucleus - Loredana Cumpana; Olivia Zanoletti; Dinesh Kankanamge; Bryan Copits; Carmen Sandi; Simone Astori (Nature Communications)
Abstract Corticotropin-releasing hormone (CRH) is a peptide associated with stress and anxiety that acts as a potent modulator throughout the nervous system. The thalamic reticular nucleus (TRN) displays high expression of the CRH receptor 1 (CRHR1), but whether CRH modulates key TRN functions, such as sleep spindle rhythmogenesis, remained unexplored. Combining polysomnographic and photometric recordings in mice, we show that CRH release in TRN during non-rapid-eye movement sleep (NREMS) oscillates with a ~50-s periodicity, anti-correlating with sleep spindle dynamics. Optogenetic manipulations of CRH release in TRN modulated NREMS fragmentation through microarousals with corresponding changes in sigma and delta power. In ex-vivo recordings, CRHR1 activation decreased the propensity of TRN neurons to fire calcium bursts. CRHR1 knockdown in parvalbumin TRN neurons prevented the effects of CRH on NREMS and TRN bursting. Thus, CRHR1 impacts NREMS by modulating thalamic excitability, providing a potential target to stabilize sleep impairments associated with stress and anxiety.